PENGEMBANGAN BAHAN AJAR SIBUDI (SINERGI BUDAYA INDONESIA) BERBANTUAN KARTU KORSA BHINNEKA BERBASIS GAMIFIKASI PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Rusman Iyonu; Candra Cuga; Aina Nurdiyanti; Nurainun; Reska Putri Ismail; Rustam I. Husain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop SIBUDI (Sinergi Budaya Indonesia) teaching materials assisted by Kartu Korsa Bhinneka based on gamification in Civics Education (PKn) learning on the material of Indonesian cultural diversity in elementary schools as a solution to the limited use of learning media in the classroom. In its implementation, the researcher applied a gamification approach with the expectation of creating an enjoyable learning process and presenting a more lively and meaningful classroom atmosphere. The development of SIBUDI teaching materials assisted by Kartu Korsa Bhinneka uses the ADDIE development model which includes five stages, namely Analyze, Design, Develop, Implement, and Evaluate. However, this research was only carried out up to the implementation stage and limited formative evaluation due to the time limitations possessed by the researcher. The validation results from material experts, media experts, language experts, and user experts show that the SIBUDI (Sinergi Budaya Indonesia) teaching materials assisted by Kartu Korsa Bhinneka based on gamification obtained an average score of 94.7% which is stated to be very feasible to be used by teachers and students in elementary schools. In addition, the results of the limited trial show a student response percentage of 92.4% which is in the very practical category. Thus, this research successfully shows that SIBUDI teaching materials assisted by Kartu Korsa Bhinneka based on gamification can become a relevant solution and provide an alternative learning media that is interesting and interactive in Civics Education learning, especially on the material of Indonesian cultural diversity. The limited trial of this research was conducted at MIM Unggulan Kota Gorontalo as the research location.